Upaya Dinas Pemberdayaan Perempuan, Perlindungan Anak dan Pemberdayaan Masyarakat Kota Pekanbaru (DP3APM) dalam Pencegahan Tindak Kekerasan Terhadap Anak di Kota Pekanbaru tahun 2024 - Rifa'i, Fatih Taufiqurrahman; Munir, Abdul (UIR PRESS, 2026)
This research is motivated by the high vulnerability of children as victims of violence, with 160 cases recorded in Pekanbaru City in 2023. The objective is to describe and analyze the efforts to prevent violence against children carried out by the Office of Women’s Empowerment, Child Protection, and Community Empowerment (DP3APM) of Pekanbaru City in 2024. This study employs a qualitative method with a case study approach. Data were collected through in-depth interviews, observation, and documentation, then analyzed using the crime prevention theory by Brantingham and Faust. The results indicate that prevention efforts were conducted comprehensively through primary prevention (establishment of community-based child protection activists, mobile